Effects of cardiac toxicity of combination therapy with hydroxychloroquine and azithromycin in COVID-19 patients - Usha Yendrapalli; Hassoun Ali; Jacqueline L. Green; Jonathan Edwards (Elsevier, 2021)
Coronavirus disease 2019 (COVID-19), which began in China, caused a global pandemic. Few studies have shown the benefit of hydroxychloroquine (HY) ± azithromycin (AZ) for treating COVID-19. Concerns of QT prolongation and increased risks of torsade's de pointes (TdP) with this combination have been raised since each agent can individually prolong the QT interval. This retrospective, observational study included hospitalized patients treated with HY and AZ from March 2020 to May 2020 at a large community hospital. Serial assessments of the QT interval were performed. Our aim is to evaluate the safety and characterize the change in QTc interval and arrhythmic events in COVID-19 patients treated with HY/AZ. A total of 21 COVID patients who received at least four days of HY and AZ were included in this study. Mean baseline was QTc 403 ms, mean maximum QTc was 440 ms, mean change in QTc was 36 ms. Only one patient (4.8%) developed prolonged QTc > 500 ms. No patient had a change in QTc of 60 ms or more. No patient developed TdP. Fifteen patients (71.4%) had hypoxia on admission, with only two patients (9.5%) required oxygen of 1−2 L at discharge. 80.9% of patients have been discharged home or inpatient rehabilitation.